Human D-aspartate Oxidase: A Key Player in D-aspartate Metabolism - Pollegioni, Loredano; Molla, Gianluca; Sacchi, Silvia; Murtas, Giulia (Frontiers in Molecular Biosciences, 2021)
In recent years, the D-enantiomers of amino acids have been recognized as natural molecules present in all kingdoms, playing a variety of biological roles. In humans, D-serine and D-aspartate attracted attention for their presence in the central nervous system. Here, we focus on D-aspartate, which is involved in glutamatergic neurotransmission and the synthesis of various hormones. The biosynthesis of D-aspartate is still obscure, while its degradation is due to the peroxisomal FAD-containing enzyme D-aspartate oxidase. D-Aspartate emergence is strictly controlled: levels decrease in brain within the first days of life while increasing in endocrine glands postnatally and through adulthood. The human D-aspartate oxidase (hDASPO) belongs to the D-amino acid oxidase-like family: its tertiary structure closely resembles that of human D-amino acid oxidase (hDAAO), the enzyme that degrades neutral and basic D-amino acids. The structure-function relationships of the physiological isoform of hDASPO (named hDASPO_341) and the regulation of gene expression and distribution and properties of the longer isoform hDASPO_369 have all been recently elucidated. Beyond the substrate preference, hDASPO and hDAAO also differ in kinetic efficiency, FAD-binding affinity, pH profile, and oligomeric state. Such differences suggest that evolution diverged to create two different ways to modulate D-aspartate and D-serine levels in the human brain. Current knowledge about hDASPO is shedding light on the molecular mechanisms underlying the modulation of the neurotransmitters D-aspartate levels in human tissues and is pushing novel, targeted therapeutic strategies. Now, it has been proposed that dysfunction in NMDA receptor-mediated neurotransmission is caused by disrupted D-aspartate metabolism in the nervous system during the onset of various disorders (such as schizophrenia): the design of suitable hDASPO inhibitors aimed at increasing D-aspartate levels thus represents a novel and useful form of therapy.